Frequency of Tuberculosis in End Stage Renal Disease (ESRD) Patients: A Cross Sectional Study - Murik Rani Tanwani; Abdul Manan Junejo; Mohammad Ali Unar; Ayesha Ejaz; Jai Kumar (Journal of the Dow University of Health Sciences)
Objective: To determine the frequency of tuberculosis (TB) and identify risk factors among end-stage renal disease (ESRD) patients undergoing maintenance hemodialysis. Methods: This cross-sectional study was conducted at the Nephrology Department of Jinnah Postgraduate Medical Centre (JPMC), Karachi, from January to March 2025. Patients aged 18 to 65 years who had been undergoing maintenance hemodialysis for at least six months were enrolled. Tuberculosis screening was performed based on symptom criteria outlined by the World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC). A diagnosis of TB was confirmed by one or more of the following: positive acid-fast bacilli (AFB) smear microscopy, a positive Gene Xpert MTB/RIF assay, or chest radiographic findings consistent with TB in the presence of clinical symptoms. Results: A total of 156 patients, median age and body mass index (BMI) were 48.5 years (35.0-60.0) and 24.1 kg/m² (20.1–27.0). TB was diagnosed in 13 (8.3%) patients. A significantly higher median difference in TB occurrence was observed among patients with older age (p-value =0.013), higher weight (p-value =0.021), higher BMI (p-value =0.014), and short duration of disease (p-value =0.019). Furthermore, diabetes mellitus was significantly more prevalent among patients with TB compared to those without TB i.e., 11 (18.3%) vs. 2 (2.1) (p-value <0.001). Conclusion: TB was diagnosed in 8.3% of ESRD patients on maintenance hemodialysis. A significantly higher occurrence of TB was observed in patients with older age, higher weight, higher BMI, shorter disease duration, and a higher prevalence of diabetes mellitus.